Comparison of gender, age, and body mass index for spatiotemporal parameters of bilateral gait pattern [version 2; peer review: 1 approved, 3 approved with reservations] - Mohammad Ahsan; Turki Abualait (F1000Research, 2022)
Background: Studies on the gaits parameters have been identified on the patient population. Most researchers confirm that the patients walk differently than normal people and they may have a greater risk of falls. Consistent finding and description of gender, age, and body mass index differences in gait studies is rare in healthy subjects.  This research was performed to compare spatiotemporal parameters of gait between gender, as per their age and body mass index level.   Methods: A cross-sectional study was conducted with forty-five young adults (F=20, M=25). Stadiometer and Physilog 4 inertial sensors were used for data collection. A gait analyzer 5.2 software (GaitUp, S.A. Lausanne, Switzerland) was used to determine spatiotemporal parameters.   Results:  Females were found with higher mean score of total double support and cadence than males. Cadence also increases with age. Obese people showed lower gait speed, cadence, and total double support. No statistically significant differences were found in any bilateral foot gait parameters with respect to gender, age, and body mass index. Conclusion: The findings of the study may be beneficial to those who have abnormal gait pattern due to age, body mass index differences, decreased muscle strength, spasticity, and joint mobility. This important information should be considered to rehabilitate patients with abnormal gait patterns to controlling dynamic balance and risk of falling.